All-Glass, Large Metalens at Visible Wavelength Using Deep-Ultraviolet Projection Lithography - Park, Joon-Suh; Zhang, Shuyan; She, Alan; Chen, Wei Ting; Lin, Peng; Yousef, Kerolos M. A.; Cheng, Ji-Xin; Capasso, Federico (AMER CHEMICAL SOC, 2019)
Metalenses, planar lenses realized by placing subwavelength nanostructures that locally impart lenslike phase shifts to the incident light, are promising as a replacement for refractive optics for their ultrathin, lightweight, and tailorable characteristics, especially for applications where payload is of significant importance. However, the requirement of fabricating up to billions of subwavelength structures for centimeter-scale metalenses can constrain size-scalability and mass-production for large lenses. In this Letter, we demonstrate a centimeter-scale, all-glass metalens capable of focusing and imaging at visible wavelength, using deep-ultraviolet (DUV) projection stepper lithography. Here, we show size-scalability and potential for mass-production by fabricating 45 metalenses of 1 cm diameter on a 4 in. fused-silica wafer. The lenses show diffraction-limited focusing behavior for any homogeneously polarized incidence at visible wavelengths. The metalens performance is quantified by the Strehl ratio and the modulation transfer function (MTF), which are then compared with commercial refractive spherical and aspherical singlet lenses of similar size and focal length. We further explore the imaging capabilities of our metalens using a color-pixel sCMOS camera and scanning-imaging techniques, demonstrating potential applications for virtual reality (VR) devices or biological imaging techniques.
Keywords: DIELECTRIC METASURFACES; CONFOCAL MICROSCOPE; POLARIZATION; OPTICS; PERFORMANCE; GENERATION; DESIGN; PHASE